"Are You a Veteran?" Understanding of the Term "Veteran" among UK Ex-Service Personnel: A Research Note. (October 2013) - Burdett, Howard; Woodhead, Charlotte; Iversen, Amy C.; Wessely, Simon; Dandeker, Christopher; Fear, Nicola T.
Different countries have varying definitions of the word "veteran, " which in turn influence the benefits that ex-Service personnel receive. However, public opinion does not necessarily reflect official definitions. This article seeks to identify whether characteristics by which UK ex-Service personnel self-identify as veterans are aligned with official policy/public opinion, and which factors are associated with self-identification as a veteran. This article utilizes data from a structured telephone interview survey of UK Armed Forces personnel. All those who had left the military by the time of interview ( n = 202) were asked whether they considered themselves to be a veteran. Their responses were recorded and analyzed. Only half of the sample considered themselves to be veterans. Definitions used by UK ex-Service personnel do not align with the official UK government definition or public perceptions of "veterans, " which tend to focus on older veterans and/or those who served in both World Wars.